In situ synthesis of titanium diboride composites through volume combustion - Yilmaz, S. O.; Evin, E.; Guler, O. (Maney Publishing, 2011)
Hard in situ synthesis of TiB2-Fe2B metal matrix composite (MMC) has been synthesised by volume combustion synthesis (VCS) reactions of Fe-FeTi-FeB system. VCS samples were characterised by SEM, EDX, XRD and DTA. Results show that it is possible to synthesise in situ structured MMC samples (with TiB2 and Fe2B phases) by VCS. Metallographic investigations show that Fe2B and TiB2 are found dispersed throughout the metal matrix, and other borides are present in microlevel patches dispersed in a eutectic matrix. The Fe-TiB2 composites sintered at temperature of 1200 degrees C consist of three different regions, i.e. alpha-Fe, TiB2 and Fe2B regions. The increase in sintering temperature to 1400 degrees C leads to a hypereutectic microstructure of the Fe-B binary system having TiB2 grains uniformly distributed throughout the matrix. A semiliquid phase sintering occurred by increasing eutectic phase transformation temperatures to 1400 degrees C, which increased the efficiency of VCS. On the other hand, increasing sintering time from 1 to 3 h decreased the volume fraction of alpha-Fe and increased the volume fraction TiB2 phase.
Keywords: X-ray diffraction; Composites; Self-propagating synthesis; Mechanical alloying; Nucleation; Phase transformation